2009
DOI: 10.1099/mic.0.030247-0
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis YtgA is an iron-binding periplasmic protein induced by iron restriction

Abstract: Chlamydia trachomatis is a Gram-negative obligate intracellular bacterium that is the causative agent of common sexually transmitted diseases and the leading cause of preventable blindness worldwide. It has been observed that YtgA (CT067) is very immunogenic in patients with chlamydial genital infections. Homology analyses suggested that YtgA is a soluble periplasmic protein and a component of an ATP-binding cassette (ABC) transport system for metals such as iron. Since little is known about iron transport in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 41 publications
6
29
1
Order By: Relevance
“…Tao . The apparent preference of YtgR for iron, instead of zinc is consistent with iron-related function of Ytg iron import system (15) and the iron responsiveness of ytgA expression (15,16).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Tao . The apparent preference of YtgR for iron, instead of zinc is consistent with iron-related function of Ytg iron import system (15) and the iron responsiveness of ytgA expression (15,16).…”
Section: Discussionsupporting
confidence: 71%
“…More recent evidence points to the Ytg system functioning in iron transport. First, the periplasmic substratebinding protein, YtgA, exhibited a significant preference toward iron over zinc or manganese in vitro (15). Also, the transcript expression of ytgA was induced in response to iron starvation of C. trachomatis (16), indicating an iron-dependent regulation of the ytg operon.…”
mentioning
confidence: 98%
“…The data represent the average Ϯ SD of the results from at least two independent experiments. to CTL0326), annotated as a Mn 2ϩ /Zn 2ϩ ABC metal transporter, has been shown to prefer iron over manganese (61). Taken together, it is plausible that Chlamydia spp.…”
Section: Figmentioning
confidence: 92%
“…The only component that has been studied in Chlamydia is YtgA, which is a homolog of the periplasmic metal-binding protein TroA. Raulston and coworkers (28) showed that C. trachomatis YtgA bound iron in vitro, and its expression was induced during iron-restrictive growth. The T. pallidum Tro transporter has been shown to import Zn 2ϩ , Mn 2ϩ , and possibly Fe 2ϩ (20), but the metal ions that are transported by the chlamydial Ytg transporter have not yet been determined.…”
Section: Discussionmentioning
confidence: 99%